Environmental Awareness On Water Pollution Through 2d Game Application (Doris) - Yong, Rong See (2023)
Water pollution is a global problem. It is important to better understand the importance of keeping our environment from water pollution. Unfortunately, most people still take little or no action to avoid or reduce the effect of water pollution. This may be because information on water pollution problems is not well communicated to the public, resulting in a lack of clear public awareness of water pollution problems. People don't know how to prevent pollution and it is difficult for people to see the actual impact of water pollution. To solve this problem, game applications is developed to enhance the public awareness about water pollution issues. The methodology adopted in this project is the ADDIE model, which makes the project development more organized. The game is developed using Unity Engine, designed using Photoshop, and using royalty free music from the internet. Platform- based games provide players with more engaging ways to interact and deliver content. The simple gameplay allows players to focus more on the delivered content and achieve the goals of this project. The final product is upload to itch.io which the player can download the game from itch.io into their PC to play. After the project is completed, there will be play testers to evaluate the project using the User Acceptance Test (UAT). The results show the game is well function and free from errors. The overall responses are positive, it also shows this game has achieved its objectives.